Chemoreception niche of Bulinus globosus, as an aid to snail control - Aboagye, I.F.; Edoh, D.A.; Kpikpi, J.E.K. (International Journal of Natural and Applied Sciences 1(5): 1-6, 2009)
Schistosomiasis has been a major public health problem especially in developing countries, where access to potable water is generally limited. Its control calls for a search for various interventions that would not only target the causative agent and human behavior, but also the snail intermediate host. This study explored the possibility of using bioactive factors from naturally occurring crude or semi-processed products including some plant parts and vegetables to control the Bulinus globosus intermediate host. In all, five (25%) of the test materials in decreasing order (pawpaw > cabbage > short banana > sugarcane > sweet orange) acted as statistically significant arrestants for the adults, but four (20%) of them in decreasing order (cabbage > unripe pawpaw > sugarcane > ripe tomato) were arrestants for the juveniles at (p< 0.01). Four (20%) of the test materials acted as significant attractants for both adult and juvenile snails in decreasing order below (unripe pawpaw > short banana > sugarcane > cabbage and cabbage > palm > sugarcane > unripe pawpaw). However, mango tree bark, neem tree bark, unripe mango, onion and cassava stem acted as significant repellents to both adult and juvenile snails. The identified attractants and arrestants for Bulinus globosus, pawpaw and cabbage, may be useful in its chemical manipulations especially as molluscicides in controlling the intermediate host snails.
Keywords: Schistosomiasis; snail; Bulinus globosus; chemoresponses; natural products